Suspected Pulmonary Embolism after Oxygen-Ozone Therapy for Low Back Pain - Chirchiglia, Domenico; Chirchiglia, Pasquale; Stroscio, Carmelino; Volpentesta, Giorgio; Lavano, Angelo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Oxygen-ozone therapy is used to treat degenerative pathology of the spine when surgery is not needed (e.g., removal of a herniated disk). Some authors have described it as a safe and effective procedure in ∼ 70 to 90% of patients. The aim of the therapy is to dehydrate the intervertebral disk and alter its contents. However, this treatment has been associated with some rare but very serious side effects. Both cardiac damage and a case of fulminant septicemia were reported. We describe a case of suspected pulmonary embolism, followed by sudden death, in an elderly woman treated with oxygen-ozone therapy for lumbar pain caused by disk protrusion. We believe a massive pulmonary embolism occurred, probably caused by an intradiskal injection that accidentally punctured a venous vessel and created emboli.
Keywords: oxygen-ozone therapy; pulmonary embolism; lower back pain